First evidence of terrestrial ambrein formation in human adipocere - von der Lühe, Barbara; Mayes, Robert W.; Thiel, Volker; Dawson, Lorna A.; Graw, Matthias; Rowland, Steven J.; Fiedler, Sabine (Scientific reports, 2019)
To date, the only known occurrence of ambrein, an important perfumery organic molecule, is in coproliths found in about one in a hundred sperm whales. Jetsam ambergris coproliths from the whale are also found occasionally on beaches worldwide. Here we report on the surprising occurrence of ambrein in human adipocere. Adipocere is a waxy substance formed post-mortem during incomplete anaerobic decomposition of soft tissues. Adipocere samples obtained from grave exhumations were analysed using gas chromatography-mass spectrometry (GC-MS). In addition to the typical fatty acids of adipocere, lesser amounts of ambrein were identified in the samples, in abundances similar to those of the major accompanying faecal steroids. The distribution of these compounds suggests that ambrein was produced post-mortem during the microbial decomposition of faecal residues and tissues. It is assumed that the adipocere matrix of saturated fatty acidsaided the preservation of ambrein over extended periods of time, because adipocere is stable against degradation. The association of ambrein formation in ageing faecal material, under moist, oxygen-depleted conditions, now requires more attention in studies of other mammalian and geological samples. Indeed, ambrein and its transformation products may be useful novel chemical indicators of aged faecal matter and decomposed bodies.